Peningkatan Persepsi Pentingnya Keterampilan Komunikasi Bisnis Yang Efektif Terhadap Pelayanan Wajib Pajak Surabaya Rungkut - Achmad Arifin (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
The purpose of the study was to determine the perception of the importance of effective interpersonal communication skills towards tax services at the Surabaya Rungkut primary tax service office, using the literature study method with a descriptive exploratory approach. The research used is qualitative and based on subordinate information. Fostering effective interaction, there are 5 things that must be considered: 1. Clarity, when communicating must use clear language and information is clearly packaged so that it is easy to understand 2. Accuracy, and accuracy related to the correct use of language and the context of communication occurs 3. The context of the information and language to be thrown out must adjust the circumstances in which communication occurs 4. The language information channel to be prepared is composed of clear channels or systematics 5. Culture on communication must be attached to culture.